Clinical Impact of CD19 Expression Assessed by Quantitative PCR in Lymphoma Patients Undergoing CAR‐T Therapy - Rafael Hernani; Laura Ventura; Begoña Heras; Alicia Serrano; Marcos Rivada; Carolina Martínez‐Ciarpaglini; Ana Benzaquén; Blanca Ferrer‐Lores; Ariadna Pérez; José Luis Piñana; Juan Carlos Hernández‐Boluda; Ignacio Arroyo; et al. (eJHaem)
ABSTRACT Introduction Current guidelines do not mandate CD19 tumor expression assessment before chimeric antigen receptor T‐cell (CAR‐T) therapy in large B‐cell lymphoma (LBCL) patients due to limitations of immunohistochemistry (IHC) or flow cytometry. Quantitative polymerase chain reaction (qPCR) offers a more sensitive alternative for detecting CD19 expression, with the primary advantage that mRNA can be easily extracted from paraffin‐embedded tissues. Methods & Results In our study, we included 51 adult patients with LBCL treated with axicabtagene ciloleucel. Among them, 16 were classified as CD19‐negative by IHC; however, qPCR reclassified six (37.5%) as CD19‐positive. We then compared the outcomes between consistently CD19‐negative (IHC−qPCR−) and CD19‐positive (IHC+ and IHC−qPCR+) patients. CD19‐negative cohort showed worse 1‐year progression‐free survival (15 vs. 45%, p = 0.044) and a trend toward shorter duration of response (29 vs. 55%, p = 0.065). Only one (10%) of the CD19‐negative patients remained alive and disease‐free at last follow‐up (6 months), having previously responded to bridge therapy. Discussion If confirmed in a large patient cohort, these findings could form the basis for modifying current patient selection criteria. Consistently negative patients may be suboptimal candidates for anti‐CD19 CAR‐T therapy. Alternative therapeutic options, such as bispecific antibodies or polatuzumab‐based regimens, could be considered for this subset of patients.